An update on congenital melanocytic nevus syndrome: A case report and literature review. (2nd August 2021) - Abdulmajid, Lilaf; Bosisio, Francesca Maria; Brems, Hilde; De Vlieger, Greet; Garmyn, Marjan; Segers, Heidi; Demaerel, Philippe; Segers, Katarina; Jansen, Katrien; Lagae, Lieven; Verheecke, Magali
Abstract: Congenital melanocytic nevus syndrome (CMNS) is a rare condition characterized by pigmented skin lesions that are usually present at birth and are associated with an increased risk of neurological abnormalities and malignant melanoma. It mostly results from a post‐zygotic NRAS mutation of neural‐derived crest cells, leading to uncontrolled cell growth. Because of the increased knowledge of the genetics underlying CMNS, targeted therapy becomes a promising treatment option. We present a case of CMNS in a newborn. Physical examination at birth showed a giant congenital melanocytic nevus, extending from the occipital to the lower lumbar region. A magnetic resonance imaging scan revealed multiple cerebral and cerebellar parenchymal lesions. Genetic analysis of the cutaneous lesions showed the presence of an NRAS Q61R mutation. The patient was treated with dermabrasion to reduce the color intensity of the nevus. However, this was complicated by recurrent wound infections and laborious wound healing. At the age of 1 year, the patient had an age‐appropriate psychomotor development, without neurological deficits.